2002
DOI: 10.1002/ajmg.10638
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 18 in a 20‐year‐old woman

Abstract: A 20-year-old female with trisomy 18 is described. Survival past infancy is rare in this disorder. Little is known concerning the factors that contribute to prolonged survival with this syndrome. This case provides an opportunity to review the management of older children and young adults with trisomy 18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 11 publications
0
33
0
1
Order By: Relevance
“…Most of the studies performed during the last 20 years (using data from between 21 and 106 children with trisomy 18) showed a mean survival of 3-14.5 days [Schinzel and Schmid, 1971;Carter et al, 1985;Goldstein and Nielson, 1988;Root and Carey, 1994;Brewer et al, 2002;Rasmussen et al, 2003]. Very few patients with trisomy 18 were reported to have survived longer than 10-15 years [Geiser and Schindler, 1969;Surana et al, 1973;Metha et al, 1986;Kelly et al, 2002;Petek et al, 2003] (see Rasmussen et al, 2003 for more detail).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies performed during the last 20 years (using data from between 21 and 106 children with trisomy 18) showed a mean survival of 3-14.5 days [Schinzel and Schmid, 1971;Carter et al, 1985;Goldstein and Nielson, 1988;Root and Carey, 1994;Brewer et al, 2002;Rasmussen et al, 2003]. Very few patients with trisomy 18 were reported to have survived longer than 10-15 years [Geiser and Schindler, 1969;Surana et al, 1973;Metha et al, 1986;Kelly et al, 2002;Petek et al, 2003] (see Rasmussen et al, 2003 for more detail).…”
Section: Introductionmentioning
confidence: 99%
“…The report of trisomy 18 in a 20-year-old woman [Kelly et al, 2002] is of interest. Unfortunately, the principal lessons to be learned from it are not well crystallized by the authors.…”
mentioning
confidence: 99%
“…However, we disagree with the authors in some of their concluding assertions. Kelly et al [2002] state that ''Parents must be advised to seek medical attention when their child becomes febrile.'' Reading such a remark, parents whose child has already died early due to overwhelming sepsis may experience guilt and/or anger because providers encouraged them to ''let go'' and did not urge them to call about a fever.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent issue of the journal, Kelly et al [2002] reported a case of a 20-year-old woman with trisomy 18. She presented to the cardiology service after two decades without cardiac care and presented with many physical stigmata of trisomy 18 and echocardiographic evaluation was consistent with tetralogy of Fallot.…”
mentioning
confidence: 99%